Mikrophonie I, Mikrophonie II, Telemusik - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1995)
MIKROPHONIE I / MICROPHONY Ifor tam-tam, 2 microphones, 2 filters with potentiometers (6 players)MIKROPHONIE II / MICROPHONY II for choir, Hammond organ, 4 ring modulatorsTELEMUSIK / TELEMUSIC Electronic MusicEdition with booklet in English (128 pages)